A value assessment system for the conservation and utilization of decentralized distilleries in the architectural heritage of the brewing industry: a case study of Yibin city, China - Yixi Wang; Bo Zhou; Xianglei Hu (Journal of Asian Architecture and Building Engineering)
With a brewing history spanning over four millennia, Yibin city is adorned with myriad traditional distilleries that have dotted its landscape since ancient times. In recent years, industrial architectural heritage has approached the forefront of cultural heritage research, presenting new opportunities and challenges for the preservation and utilization of industrial architectural heritage sites, including distilleries. Employing field investigations and a multidisciplinary approach, this study uses data on 62 distilleries that are industrial architectural heritage sites. The analysis delves into the distribution, composition, and architectural features of the sample data, considering both production and nonproduction elements. Subsequently, the quantification of historical, societal, technological, artistic, and economic value enables an assessment, establishing an appropriate evaluation system. The research outcomes are intended to offer technical support for the conservation and utilization of heritage sites in the brewing industry, while concurrently serving as a reference for the preservation and utilization of distinctive architectural buildings in local industrial heritage sites.